pls answer to my questions
Attachments:
![](https://hi-static.z-dn.net/files/d3f/103322c881162f2e7446f249e8661b1f.jpg)
Answers
Answered by
1
x^2 - 5x + 7 = 0
third term = (1/2 (-5))^2
= (-5/2)^2
= 25/4
x^2-5x = -7
adding 25/4 on both sides
x^2-5x +25/4=+7+25/4
(x-5/2)^2=-28+25/4
(x-5/2)^2=-3/4
taking Square root
x-5/2 = +- √3/2
x-5/2= +√3/2
or x-5/2= -√3/2
X = √3/2+5/2 or X = -√3/2+5/2
X =√3+5/2 or X =-√3+5/2
I hope this helps u...
plz mark as brainlist...
third term = (1/2 (-5))^2
= (-5/2)^2
= 25/4
x^2-5x = -7
adding 25/4 on both sides
x^2-5x +25/4=+7+25/4
(x-5/2)^2=-28+25/4
(x-5/2)^2=-3/4
taking Square root
x-5/2 = +- √3/2
x-5/2= +√3/2
or x-5/2= -√3/2
X = √3/2+5/2 or X = -√3/2+5/2
X =√3+5/2 or X =-√3+5/2
I hope this helps u...
plz mark as brainlist...
tanayajagadale:
and u
Similar questions
Physics,
8 months ago
English,
8 months ago
English,
8 months ago
Science,
1 year ago
Social Sciences,
1 year ago